2016
DOI: 10.1556/168.2016.17.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Coleoptera assemblages of pine forests depends on the distance to the source of nitrogen pollution

Abstract: The paper analyzed the changes of beetle assemblages in the litter layer of eutrophic pine forests in the zone polluted by a nitrogen fertilizer plant Joint Stock Company "Achema" (Lithuania). We hypothesized that abundance, diversity and life traits of beetle assemblages depend on the distance from the pollution source. The samples of the litter layer were taken from pine stands at the distances of 3, 5, 10 and 20 km from the plant. The PCA and GLM analyses were used to reduce the number of variables to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…They claim that mechanical soil preparation eliminates the original microsites and alters microclimatic conditions, which cause the disappearance of sensitive specialist species. Also Tamutis and Skłodowski (2016) concluded that the establishment of cleared forest and ploughing had a negative influence on forest rove beetle species. A similar relationship was observed in the case of carabid beetles and spiders.…”
Section: Discussionmentioning
confidence: 99%
“…They claim that mechanical soil preparation eliminates the original microsites and alters microclimatic conditions, which cause the disappearance of sensitive specialist species. Also Tamutis and Skłodowski (2016) concluded that the establishment of cleared forest and ploughing had a negative influence on forest rove beetle species. A similar relationship was observed in the case of carabid beetles and spiders.…”
Section: Discussionmentioning
confidence: 99%